2020
DOI: 10.35609/jfbr.2020.5.2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Are Corporate Governance Mechanisms, Corporate Strategy, and Corporate Financial Characteristics Related to Earnings Management?

Abstract: Objective – This study aims to examine the effect of corporate governance and several factors of corporate financial characteristics on earnings management. Corporate governance mechanisms such as an independent board, board size, and audit committee size are expected to be able to limit the ability of management to carry out earnings management. Meanwhile, a company's financial characteristics such as corporate strategy, company age, operating cash flow, company growth, profitability, company size and leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…Stakeholder Theory is critical for comprehending the concept of a company's diversification strategy; it explains how the company will conduct business responsibly and sustainably [47]. Diversification is believed to improve the company's financial performance, and it is hoped that it will be better able to implement and disclose corporate sustainability programs.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholder Theory is critical for comprehending the concept of a company's diversification strategy; it explains how the company will conduct business responsibly and sustainably [47]. Diversification is believed to improve the company's financial performance, and it is hoped that it will be better able to implement and disclose corporate sustainability programs.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil kinerja perusahaan digambarkan dan dirangkum ke dalam suatu laporan yang disajikan oleh pihak manajemen, yaitu laporan keuangan. Banyak informasi penting tercakup dalam laporan keuangan yang telah disiapkan, seperti informasi mengenai pendapatan perusahaan hingga informasi terkait laba dan rugi yang dihasilkan oleh perusahaan dalam periode tertentu (Tonay dan Sutrisno 2020). Menurut Wulandari dan Suganda (2021), salah satu indikator yang dapat digunakan untuk menilai baik buruknya kinerja suatu perusahaan adalah informasi laba yang tercantum dalam laporan keuangan.…”
Section: Pendahuluanunclassified
“…The goal of having an independent board of directors is to reduce the possibility of information imbalances and untrustworthy management choices (Abata and Migiro, 2016). According to Tonay and Sutrisno's (2020) empirical evidence from Indonesian nonfinancial firms, having an independent board of directors aids in the reduction of earnings management activities since it provides more efficient oversight and supervision than a nonindependent board. Previous research has also demonstrated a beneficial association among the size of the board, the independence of board members, the number of board meetings and the quality of oversight in firms (Kapoor and Goel, 2017), all of which lead to the reduction of opportunistic activities by managers (Usman et al, 2019).…”
Section: Board Characteristics and Earnings Managementmentioning
confidence: 99%